Quantitative and Qualitative Analysis of the Mental Models Deployed by Undergraduate Students in Explaining Thermally Activated Phenomena - Claudio Fazio; Onofrio Rosario Battaglia; Rosa Maria Sperandeo-Mineo (Karolinum Press, 2017)
In this contribution we describe a research aimed at pointing out the quality of mental models undergraduate engineering students deploy when asked to create explanations for phenomena/processes and/or use a given model in the same context. Student responses to a specially designed written questionnaire are initially analyzed using researcher-generated categories of reasoning, based on the Physics Education Research literature on student understanding of the relevant physics content. The inferred students' mental models about the analyzed phenomena are categorized as practical, descriptive, or explanatory, based on an analysis of student responses to the questionnaire. A qualitative analysis of interviews conducted with students after the questionnaire administration is also used to deepen some aspects which emerged from the quantitative analysis and validate the results obtained.